2018
DOI: 10.1016/j.bbamcr.2018.05.005
|View full text |Cite
|
Sign up to set email alerts
|

NCS-1 is a regulator of calcium signaling in health and disease

Abstract: Neuronal Calcium Sensor-1 (NCS-1) is a highly conserved calcium binding protein which contributes to the maintenance of intracellular calcium homeostasis and regulation of calcium-dependent signaling pathways. It is involved in a variety of physiological cell functions, including exocytosis, regulation of calcium permeable channels, neuroplasticity and response to neuronal damage. Over the past 30 years, continuing investigation of cellular functions of NCS-1 and associated disease states have highlighted its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
39
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 144 publications
1
39
0
1
Order By: Relevance
“…Among the 3 targets, we focused on NCS1 because its aberrant expression significantly predicted poor prognosis in patients. The NCS1 protein is a member of the NCS family, which harbors a functional Ca 2+ binding domain and N ‐terminally myristoylated site . Previous studies have reported that NCS1 is a multifunctional protein involved in exocytosis, neurite outgrowth, neuroprotection, axonal regeneration, and nuclear Ca 2+ regulation .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the 3 targets, we focused on NCS1 because its aberrant expression significantly predicted poor prognosis in patients. The NCS1 protein is a member of the NCS family, which harbors a functional Ca 2+ binding domain and N ‐terminally myristoylated site . Previous studies have reported that NCS1 is a multifunctional protein involved in exocytosis, neurite outgrowth, neuroprotection, axonal regeneration, and nuclear Ca 2+ regulation .…”
Section: Discussionmentioning
confidence: 99%
“…The NCS1 protein is a member of the NCS family, which harbors a functional Ca 2+ binding domain and N ‐terminally myristoylated site . Previous studies have reported that NCS1 is a multifunctional protein involved in exocytosis, neurite outgrowth, neuroprotection, axonal regeneration, and nuclear Ca 2+ regulation . Furthermore, NCS1 interacts with various proteins to control their functions .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NCS1 interacts with a wide range of proteins, including the inositol 1,4,5‐ tris phosphate receptor (InsP3R), dopamine receptor type 2 (D2R), and phosphatidylinositol 4‐OH kinase (PI4K) (35, 36). Through its protein‐protein interactions, NCS1 regulates vital cellular processes such as neurotransmitter release (32), neurite outgrowth and neuronal survival (37, 38), spatial memory formation (31), and the InsP3R signaling pathway (39, 40).…”
mentioning
confidence: 99%